2019
DOI: 10.3390/atmos10040183
|View full text |Cite
|
Sign up to set email alerts
|

Congruence Evaluation of Mercury Pollution Patterns Around a Waste Incinerator over a 16-Year-Long Period Using Different Biomonitors

Abstract: To date, there has been an ever-increasing interest in complementary air monitoring techniques, which may fill the deficiencies of air quality networks. The present work reports the results concerning five biomonitoring surveys (BSs) performed in the proximity of a waste incinerator (WI) over a 16-year period. Hg emission related to the WI activity was monitored by means of both active and passive BSs based on three photosynthetically-active biomonitors (i.e., two epiphytic lichens: Pseudevernia furfuracea and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Although the ability of lichens to take up Hg and provide accurate patterns of Hg contamination around emission sources is well documented [ 11 , 19 , 20 , 21 , 22 , 23 , 24 ], information on their ability to reflect the decreasing environmental availability of this element is minimal and contrasting. Walther et al [ 25 ] found an efficient long-term ability of lichens to release the accumulated Hg, as a consequence of the phase-out of the contamination source (a chlor-alkali facility), but Godinho et al [ 26 ] and Vannini et al [ 15 ] reported the lack of long- and short-term release of accumulated Hg over time.…”
Section: Introductionmentioning
confidence: 99%
“…Although the ability of lichens to take up Hg and provide accurate patterns of Hg contamination around emission sources is well documented [ 11 , 19 , 20 , 21 , 22 , 23 , 24 ], information on their ability to reflect the decreasing environmental availability of this element is minimal and contrasting. Walther et al [ 25 ] found an efficient long-term ability of lichens to release the accumulated Hg, as a consequence of the phase-out of the contamination source (a chlor-alkali facility), but Godinho et al [ 26 ] and Vannini et al [ 15 ] reported the lack of long- and short-term release of accumulated Hg over time.…”
Section: Introductionmentioning
confidence: 99%
“…Burning of fossil fuels and coal [20] Metal mining [1] Fertilizers, pesticides, and other chemical manufacturing [21] Incineration of domestic and industrial waste [22] Volcanic eruption, first fire [23] Hydrosphere exposure…”
Section: Exposure Groups Sources Referencementioning
confidence: 99%
“…However, due to the high costs, the monitoring networks for Hg pollution assessment are still characterized by low temporal (generally on an annual basis) and spatial coverage [ 15 ]. For the above reasons, there is growing interest in alternative air monitoring techniques such as plant, insects, lichens, and mosses that can provide reliable time-integrated estimates of air pollution in a given area at low cost [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. In particular, bees and their products such as honey, propolis, and pollen have been proposed as bioindicators of environmental Hg contamination [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%